New tools for maggot debridement therapy research: From the establishment of qRT-PCR to the characterization of Lucilia sericata Urate Oxidase - Baumann, Andre; Justus Liebig University Giessen (My University, 2017)
Maggot debridement therapy (MDT) is an U.S. Food and Drug Administration (FDA) as well as European Medicines Agency (EMA) approved treatment for various chronic and recalcitrant wounds. MDT was successfully applied in numerous case studies (Sherman 2002; Sherman 2003) and shown to have beneficial effects on wound debridement, disinfection and hastened healing processes (Sherman 2014). Larval secretions and excretions (E/S) represent a complex mixture of enzymes, AMPs and small molecules and as such serves as a rich source of new therapeutics (Sherman 2014). Unfortunately, the complexity of this mixture makes it very hard to decipher the exact roles and benefits of individual components in the wound healing process and requires more detailed studies (Davydov 2011).This thesis is based on two parts. The first part, published in PLOS ONE (Baumann et al. 2015), focused on the establishment of a qRT-PCR approach by investigating tissue specific expression stability of 10 candidate reference genes in immune challenge experiments. Quantitative RT-PCR serves as a golden standard in the field of gene expression (Bustin et al. 2009; Nolan et al. 2006) and its establishment in L. sericata serves as an important tool for identification and validation of genes involved in maggot therapy. My study shows that the combination of three reference genes RPLP0, EF1alpha and RPS3 provides reliable normalization of L. sericata expression data among all tested samples, thus allowing for the first time the precise normalization of gene expression in larval tissues involved in production of E/S. The methods of tissue sample preparation and gene expression analysis established during this thesis also contributed to Beckert et al. (2015) and Beckert et al. (2016). Reference genes were applied in Pöppel et al. (2016) and Franta et al. (2016).Second part of this thesis, submitted to Insect Biochemistry and Molecular Biology (Baumann et al. 2016), focuses on recombinant production and characterization of L. sericata Urate Oxidase (UO) an enzyme that exclusively creates allantoin, which contributes to the wound healing process (Araujo et al. 2010; DiSalvo 2002). I was the first to produce and characterize an insect UO. Recombinant UO was produced using E. coli expression system, purified via IMAC (denaturing chromatography), refolded and tested for its pH optimum (in the alkaline), temperature optimum (20-25 °C), competitive inhibition (typical for UO), cofactors (cofactor independent) and stability (short shelf life). Furthermore, I monitored the presence of L. sericata UO on mRNA as well as protein level in various L. sericata tissues and showed that both UO gene as well as native UO localize predominately inside Malpighian tube cells sharing strictly cytosolic localization. Based on these data it can be assumed that allantoin is produced by UO to remove uric acid from the insect hemolymph by the Malpighian tubes and is excreted via the hindgut as nitrogenous waste product. Those findings support the hypothesis that not only actively secreted molecules, but also excretion products contribute to the beneficial effects of MDT.

Die Maden-Débridement-Therapie (MDT) ist eine durch die U.S. Food and Drug Administration (FDA) und European Medicines Agency (EMA) zugelassene Behandlung für verschiedene chronische und hartnäckige Wunden. MDT wurde in zahlreichen Fallstudien erfolgreich angewendet (Sherman 2002; Sherman 2003), welche die fördernden Eigenschaften in Débridement, Desinfektion sowieso beschleunigter Wundheilung zeigten (Sherman 2014). Maden Sekretions- und Exkretionsprodukte (E/S) sind eine komplexe Mischung aus Enzymen, AMPs und niedermolekularen Verbindungen und als solches eine reiche Quelle für neue Therapeutika (Sherman 2014). Die Komplexität dieser Mischung macht es sehr schwer, die exakte Rolle und die positiven Effekte einzelner Komponenten im Heilungsprozess zu bestimmen und macht detailliertere Analysen erforderlich (Davydov 2011). Diese Arbeit besteht aus zwei Teilen. Der erste Teil, wie in Baumann et al. (2015) publiziert, hat den Schwerpunkt in der Etablierung eines qRT-PCR Ansatzes zur gewebespezifischen Untersuchung der Expressionsstabilität von 10 Referenzgen-Kandidaten in Immunisierungs-Experimenten. Quantitative RT-PCR ist der Goldstandart im Bereich der Genexpressionsanalyse (Bustin et al. 2009; Nolan et al. 2006) und seine Etablierung in L. sericata stellt ein wichtiges Werkzeug für die Identifizierung und Validierung von Genen, die an der Madentherapie beteiligt sind, dar. Meine Arbeit zeigt, dass die Kombination der drei Referenzgene RPLP0, EF1alpha und RPS3 eine verlässliche Normalisierung von L. sericata Expressionsdaten in allen getesteten Proben ermöglicht. Dies erlaubt zum ersten Mal die präzise Normalisierung der Genexpression in Madengeweben, welche eine Rolle in der Produktion von E/S spielen. Die Methoden zur Bearbeitung von Gewebeproben und zur Genexpressionsanalyse, die im Rahmen dieser Arbeit etabliert wurden, haben auch zu den Publikationen Beckert et al. (2015) und Beckert et al. (2016) beigetragen. Außerdem fanden die Referenzgene bereits Anwendung in Pöppel et al. (2016) und Franta et al. (2016).Im zweiten Teil dieser Arbeit, eingereicht als Baumann et al. (2016) (Insect Biochemistry and Molecular Biology) wurde die Uratoxidase (UO) von L. sericata heterolog exprimiert und charakterisiert. Dieses Enzym erzeugt Allantoin, welches zum Wundheilungsprozess beiträgt (Araujo et al. 2010; DiSalvo 2002). Ich war der Erste, der eine Insekten UO exprimiert und charakterisiert hat. Das rekombinante Enzym wurde in E. coli exprimiert, mittels IMAC unter denaturierenden Bedingungen aufgereinigt, rückgefaltet und hinsichtlich pH-Optimum (im Basischen), Temperaturoptimum (20-25 °C), kompetitiver Inhibition (typisch für UOs), Kofaktoren (Kofaktor unabhängig) und Stabilität (kurze Halbwertszeit) untersucht. Des Weiteren wurde L. sericata UO sowohl auf mRNA- als auch auf Proteinebene in verschiedenen L. sericata Geweben lokalisiert. Ich konnte zeigen, dass sowohl die UO-mRNA als auch das native UO-Enzym vorwiegend in den Zellen der Malpighischen Gefäße und dort in beiden Fällen strikt zytosolisch lokalisiert ist. Basierend auf diesen Ergebnissen kann angenommen werden, dass Allantoin durch UO produziert wird, um Harnsäure aus der Insektenhämolymphe über die Malpighischen Gefäße zu entfernen und über den Hinterdarm als Stickstoff-Abfallprodukt zu exkretieren. Diese Ergebnisse unterstützen die Hypothese, dass nicht nur aktiv sekretierte Moleküle, sondern auch Exkretionsprodukte zu den positiven Effekten der MDT beitragen.
Keywords: ddc:570